2009
DOI: 10.1111/j.1532-5415.2009.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Emergency Readmissions and Better Quality of Life for Older Adults at Risk of Hospital Readmission: A Randomized Controlled Trial to Determine the Effectiveness of a 24‐Week Exercise and Telephone Follow‐Up Program

Abstract: Early introduction of an individualized exercise program and long-term telephone follow-up may reduce emergency health service utilization and improve quality of life of older adults at risk of hospital readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
286
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(302 citation statements)
references
References 29 publications
7
286
3
5
Order By: Relevance
“…Data regarding the effectiveness of pre-and postdischarge interventions have been mixed, but targeting these lower acuity admissions may be more cost-effective than interventions addressing long-term outpatient disease management. [38][39][40][41][42][43][44][45] Primary care access and ED utilization patterns have been examined in multiple studies looking at risk for admission, with varying results. 4,6,12,13,[46][47][48] In our study, self-reported ambulatory care did not differ between the patients with strongly acuity-driven and moderately/weakly acuity-driven admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the effectiveness of pre-and postdischarge interventions have been mixed, but targeting these lower acuity admissions may be more cost-effective than interventions addressing long-term outpatient disease management. [38][39][40][41][42][43][44][45] Primary care access and ED utilization patterns have been examined in multiple studies looking at risk for admission, with varying results. 4,6,12,13,[46][47][48] In our study, self-reported ambulatory care did not differ between the patients with strongly acuity-driven and moderately/weakly acuity-driven admissions.…”
Section: Discussionmentioning
confidence: 99%
“…The trials were conducted in a broad variety of international health care systems. Eleven were from the United States; [26][27][28][29][30][31][32][33][34][35][36] three from Hong Kong; [37][38][39] two from Australia; 40,41 and one each from Germany, 42 Spain, 43 Canada, 44 Sweden, 45 the United Kingdom, 46 Ireland, 47 Italy, 48 China, 49 Taiwan, 50 and a collaboration between Spain and Belgium. 51 The studies' sample sizes ranged from 41 to 1,001 people.…”
Section: Study Resultsmentioning
confidence: 99%
“…60 At 6 months this intervention within a cohort of 128 frail older patients resulted in significantly fewer readmissions (22 v. 47%; P = 0.007) and emergency visits to GPs (25 v. 67%; P < 0.001).…”
Section: Studies Of Integrated Pre-and Postdischarge Multicomponent Imentioning
confidence: 99%